Supramolecular ionic polymer stripping nano-montmorillonite and preparation method thereof

By introducing multifunctional imidazole and heteropolyacid anions between the montmorillonite layers, the problem of insufficient dispersion and heat resistance of montmorillonite is solved, and the barrier properties of the membrane materials are significantly improved. It is suitable for High temperature processing.

CN119307009APending Publication Date: 2025-01-14NINGBO RUICHENG PACKING MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310856830.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The dispersion and heat resistance of montmorillonite in the existing polymer/layered inorganic nanocomposite films are insufficient, and cannot meet the requirements of high-temperature processing and barrier properties.

Method used

The multifunctional imidazole is used as a cation to bind to heteropolyacid anion, and supramolecular ion polymer is formed between the montmorillonite layers by in-situ intercalation method, expanding the spacing between the montmorillonite layers to achieve its high dispersion and peeling structure.

Benefits of technology

It improves the uniform dispersion and thermal stability of montmorillonite in polymer materials, significantly improves the barrier properties of film materials, and is suitable for processing of substrates such as polyamide and polyester.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307009A_ABST
    Figure CN119307009A_ABST
Patent Text Reader

Abstract

The invention discloses supramolecular ionic polymer stripping nano montmorillonite and a preparation method thereof. The MMT interlayer contains a supramolecular ionic polymer composed of melamine cations, multifunctional imidazole cations and heteropolyacid anions, and has a stripping structure. The method comprises the following steps: firstly, loading melamine cations on an MMT sheet layer by utilizing an aqueous solution ion exchange method, then introducing heteropolyacid anions and multifunctional imidazole cations with different structures into an MMT interlayer, and forming a supramolecular ionic polymer between the MMT layers through an in-situ intercalation method, so that the MMT layered structure is expanded to achieve a stripping structure. On one hand, MMT lamellas can be uniformly dispersed in a polymer matrix, and on the other hand, an ionic polymer formed by multifunctional imidazole cations and heteropolyacid anions has good thermal stability and can meet the high-temperature processing requirement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polymer auxiliary agent, in particular to a supramolecular ion polymer exfoliated nano-montmorillonite (C-MMT) and a preparation method thereof. Background Art

[0002] With the rapid development of modern commerce and logistics industries, the demand for packaging materials is increasing, which has promoted the technological progress of the global packaging industry. Packaging needs to be able to maintain the stability of the internal environment, protect the quality or performance of the packaged objects and extend their shelf life. The key core indicator is barrier performance. In particular, in order to preserve freshness and quality of food, medicine, electronic components, military supplies, etc., higher requirements are placed on the barrier properties of packaging materials. Barrier property refers to the ability of a material to prevent oxygen, water vapor, organic gas, light, heat and other penetrating objects from penetrating from the high-concentration side through the barrier material to the low-concentration side. The barrier properties of general materials mainly include oxygen barrier, moisture barrier, light barrier, flame retardancy, etc.

[0003] Early barrier film materials were represented by films such as ethylene-vinyl alcohol copolymer (EVOH), polyamide (PA), polyvinylidene chloride (PVDC), and polyvinyl alcohol (PVA). Driven by the strong demand for products in the fields of food and beverage, medical, and chemicals, the requirements for packaging barrier properties have become increasingly stringent. A variety of high-barrier film materials with excellent performance have been developed, including multi-layer polymer composite films, vacuum evaporation composite films, polymer / layered nanocomposite films, etc. Among them, polymer / layered inorganic nanocomposite films are layered inorganic fillers that can form nano-sized structural micro-regions dispersed in polymers to form nanocomposite films. The nanosheet structure of the filler can block gas penetration, improve the air tightness of the material, and significantly improve the barrier properties of the polymer. At present, layered nanofillers such as MMT and layered double hydroxides (LDHs) have become a hot research topic with their unique structure and excellent performance.

[0004] The key to preparing polymer / layered inorganic nanocomposite membranes is the dispersion of layered nanofillers. How to make them uniformly dispersed requires comprehensive consideration of the characteristics of inorganic and polymer matrices. Montmorillonite (MMT) is a layered silicate mineral. Because its crystal layers are negatively charged, in order to maintain the electrical neutrality of the system, the sheets will adsorb some hydrated cations, so that MMT has the ability to exchange with other cations. Therefore, organic cations can be introduced into the interlayers by ion exchange, thereby achieving intercalation and exfoliation of MMT. The more commonly used modification method is to use long-chain quaternary ammonium salts as intercalation agents to modify clay, so that the interlayer spacing of clay is expanded, thereby improving its compatibility and dispersibility with the matrix. However, the organic intercalation agents currently used in the market are often small molecular structures, with insufficient thermal stability, and the exfoliation effect is not ideal. Therefore, the effect of high dispersion can only be achieved through in-situ composite methods. The market urgently needs to find a more suitable exfoliation and dispersion method to achieve high dispersion of MMT and meet the processing requirements of materials such as polyamide MXD6.

[0005] Heteropolyacids are a class of oxygen-containing polyacids composed of heteroatoms (such as P, Si, Fe, Co, etc.) and polyatoms (such as Mo, W, V, Nb, Ta, etc.) coordinated and bridged by oxygen atoms in a certain structure. Catalytic activity , good stability, is a promising green catalyst. Moreover, the heteropolyacid anions can form supramolecular structures by combining with organic cations. The reaction synthesis is simple, and by changing the type and structure of cations and reaction conditions, its supramolecular structure and performance can be easily adjusted, thereby changing the interlayer spacing of MMT and achieving a high dispersion effect.

[0006] Although there have been many reports on MMT modification, there has been no public report on the use of multifunctional imidazole as a cation and the introduction of heteropolyacid anions into the interlayer of MMT to form a high temperature resistant film. This patent introduces multifunctional imidazole as a cation into the MMT layer, and at the same time uses the in-situ intercalation method to introduce heteropolyacid anions into the interlayer of MMT to peel off the MMT layer, thereby preparing a supramolecular ionic polymer peeling nano-MMT for application in the field of polymer material barrier. Summary of the invention

[0007] In view of the above-mentioned defects of the prior art, an object of the present invention is to provide a supramolecular ionic polymer exfoliated nano-montmorillonite.

[0008] To solve the above problems, the technical solution of the present invention is: a supramolecular ionic polymer exfoliated nano-montmorillonite, which contains melamine cations, multifunctional imidazole cations and heteropolyacid anions between its layers, and the three form supramolecular ionic polymer compounds through ionic bonds.

[0009] Furthermore, the chemical structural formula of the heteropolyacid anion is [PW 12 O 40 ] 3- 、[PMo 12 O 40 ] 3- , [BW 12 O 40 ] 3- 、[BMo 12 O 40 ] 3- 、[SiW 12 O 40 ] 4- 、[SiMo 12 O 40 ] 4- One of them.

[0010] Furthermore, the chemical structural formula of the multifunctional imidazolium cation is:

[0011]

[0012] The present invention also provides a method for preparing supramolecular ionic polymer exfoliated nano-montmorillonite, firstly, melamine salt is loaded onto MMT sheets by aqueous solution ion exchange method, then heteropolyacid anions and multifunctional imidazole cations of different structures are introduced into the MMT interlayer, and supramolecular ionic polymer ionic compounds are formed between the MMT layers by in-situ intercalation method, so that the MMT layered structure is expanded to achieve the exfoliation structure.

[0013] Furthermore, the preparation method comprises the following steps:

[0014] (1) A certain amount of MMT is dissolved in water to form a uniform and stable MMT suspension with a mass fraction of 1% to 10%, and the temperature is gradually raised to 50 to 90°C, stirred for 1 to 6 hours, and set aside;

[0015] (2) slowly adding a 0.1-1 mol / L melamine phosphate solution to the MMT suspension in step (1) above, and reacting at 60-80° C. for 1.5-3 h; then filtering, washing, and redispersing, and repeating this operation 2-3 times to wash away excess unexchanged melamine phosphate, and finally forming a melamine-montmorillonite suspension with a mass fraction of 1% to 10%;

[0016] (3) firstly, adding a heteropolyacid containing different anions dropwise into the melamine-montmorillonite suspension of step (2), then adding a polyfunctional imidazole bromide dropwise into the suspension, and then heating to 40-60° C. and reacting for 1-2 hours;

[0017] (4) The product after the reaction in step (3) is filtered and washed with water for 3 to 5 times, and then vacuum dried at 60 to 80° C. for 6 to 8 hours, and then crushed in a pulverizer.

[0018] Furthermore, in step (1), the MMT is sodium-based MMT or organic-modified MMT, and its cation exchange capacity is 60 to 120 mmol / 100 g.

[0019] Furthermore, in step (2), the molar amount of melamine cations in the melamine phosphate solution is 1.2 to 2 times the total ion exchange amount CEC in the MMT suspension.

[0020] Furthermore, in step (3), the mass of the heteropoly acid is 1.1 to 1.5 times that of montmorillonite, and the concentration is 0.1 to 1 mol / L.

[0021] Furthermore, the anion of the heteropolyacid is [PW 12 O 40 ] 3- or [PMo 12 O 40 ] 3- or [BW 12 O 40 ] 3- or [BMo 12 O 40 ] 3- When the structural formula of the multifunctional imidazole bromide salt is When the molar ratio of the polyfunctional imidazolium cation to the heteropolyacid anion is 1;

[0022] The structural formula of the multifunctional imidazole bromide is When the molar ratio of the imidazolium cation to the heteropolyacid anion is 1.5 / 1;

[0023] The anion of the heteropoly acid is [SiW 12 O 40 ] 4- 、[SiMo 12 O 40 ] 4- When the structural formula of the multifunctional imidazole bromide salt is When the molar ratio of the imidazolium cation to the heteropolyacid anion is 4 / 3;

[0024] The structural formula of the multifunctional imidazole bromide is

[0025] When the molar ratio of the imidazolium cation to the heteropolyacid anion is 2 / 1.

[0026] The beneficial effects of the present invention are:

[0027] 1: The preparation process of the present invention is easy to operate and can be designed. By introducing melamine cations with a capacity expansion effect into MMT, heteropolyacid anions and multifunctional imidazole cations with different contents and structures can be introduced in a targeted manner according to the characteristics of the material matrix.

[0028] 2: The present invention utilizes an in-situ intercalation method to introduce anions and cations into the MMT interlayer, and through ion polymerization, the sheet structure is opened to obtain a peeling structure, so that the MMT sheet can be evenly dispersed in the matrix to play a barrier role.

[0029] 3: The present invention can solve the shortcomings of traditional organic modified MMT, such as insufficient heat resistance and inability to meet high temperature processing.

[0030] 4: The present invention is easy to produce and industrialize, and can greatly improve the barrier properties of membrane materials; the supramolecular ionic polymer exfoliated nano-MMT with high dispersion characteristics of the present invention can be uniformly dispersed in matrices such as polyamide 6, polyamide MXD6, and polyester PET. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The XRD diagram of MMT before and after modification in Example 1 of the present invention, a is sodium-based MMT (Na-MMT); b is melamine-montmorillonite (N-MMT); c is C-MMT-1. It can be seen from the figure that the XRD diffraction peak of C-MMT-1 completely disappears, which indicates that the layered compact structure is opened and an MMT with an exfoliated structure is obtained.

[0032] Figure 2 This is the TGA diagram of C-MMT-1, which shows that it has good thermal stability. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below in conjunction with embodiments:

[0034] The invention discloses a supramolecular ion polymer exfoliated nano-montmorillonite, which contains melamine cations, multifunctional imidazole cations and heteropolyacid anions between its layers, and the three form supramolecular ion polymer compounds through ionic bonds.

[0035] Example 1

[0036] Take 100g of sodium-based MMT with an ion exchange capacity of 60mmol / 100g, add 900ml of deionized water to form a suspension with a mass fraction of 10%, and stir at 80℃ for 2h;

[0037] Take 0.12 mol (molar amount is twice the total amount of MMT ion exchange) of melamine phosphate and prepare it into an aqueous solution with a concentration of 0.1 mol / L, slowly add the solution dropwise to the sodium-based MMT suspension, heat to 80°C and react for 3 hours, filter, wash and then disperse and repeat for 3 times, and finally obtain a suspension of melamine-montmorillonite (melamine-montmorillonite (N-MMT)) with a mass fraction of 10%.

[0038] Take 150g of H3[PW 12 O 40 ], add deionized water to prepare a solution with a concentration of 1 mol / L, and then take an equal molar An aqueous solution (concentration of 1 mol / L) was added dropwise to the above suspension, then heated to 80°C and reacted for 2 hours; filtered and washed with water three times, then vacuum dried at 60°C for 8 hours, and crushed in a grinder to obtain C-MMT-1 with an exfoliated structure.

[0039] Example 2

[0040] Take 200g of sodium-based MMT with an ion exchange capacity of 80mmol / 100g, add 1800ml of deionized water to form a suspension with a mass fraction of 10%, and stir at 70℃ for 3h;

[0041] Take 0.24 mol (molar amount is 1.5 times the total amount of MMT ion exchange) of melamine acetate and prepare it into an aqueous solution with a concentration of 0.1 mol / L, slowly add the solution to the sodium-based MMT suspension, keep the temperature at 70°C and react for 2 hours, filter, wash and then disperse and repeat 3 times in sequence to finally obtain a melamine-montmorillonite (N-MMT) suspension.

[0042] Take 220g of H3[PMo 12 O 40 ], add deionized water to prepare a solution with a concentration of 1 mol / L, and then take an equal molar An aqueous solution (concentration of 0.5 mol / L) was added dropwise to the above suspension, then heated to 50°C and reacted for 2 hours; filtered and washed with water three times, then vacuum dried at 70°C for 7 hours, and crushed in a grinder to obtain C-MMT-2 with an exfoliated structure.

[0043] Example 3

[0044] Take 100g of organic modified MMT with an ion exchange capacity of 100mmol / 100g, add 1900ml of deionized water to form a suspension with a mass fraction of 5%, and stir at 70℃ for 4h;

[0045] Take 0.14 mol (molar amount is 1.4 times the total amount of MMT ion exchange) of melamine phosphate and prepare it into an aqueous solution with a concentration of 0.1 mol / L, slowly add the solution to the sodium-based MMT suspension, keep the temperature at 70°C and react for 1.5 hours, filter, wash and then disperse and repeat twice in sequence to finally obtain a melamine-montmorillonite (N-MMT) suspension.

[0046] Take 220g of H3[BW 12 O 40 ], add deionized water to prepare a solution with a concentration of 1 mol / L, and then take an equal molar An aqueous solution (concentration of 0.5 mol / L) was added dropwise to the above suspension, then heated to 50°C and reacted for 2 hours; filtered and washed with water three times, then vacuum dried at 70°C for 7 hours, and crushed in a grinder to obtain C-MMT-3 with an exfoliated structure.

[0047] Example 4

[0048] Take 100g of sodium-based MMT with an ion exchange capacity of 120mmol / 100g, add 900ml of deionized water to form a suspension with a mass fraction of 10%, and stir at 60℃ for 5h;

[0049] Take 0.144 mol (molar amount is 1.2 times the total amount of MMT ion exchange) of melamine carbonate and prepare it into an aqueous solution with a concentration of 0.1 mol / L, slowly add the solution to the sodium-based MMT suspension, react at 60°C for 3 hours, filter, wash and then disperse and repeat 3 times to finally obtain a melamine-montmorillonite (N-MMT) suspension.

[0050] Take 150g of H3[BMo 12 O 40 ], add deionized water to prepare a solution with a concentration of 1 mol / L, and then take an equal molar An aqueous solution (concentration of 1 mol / L) was added dropwise to the above suspension, then heated to 60°C and reacted for 2 hours; filtered and washed with water three times, then vacuum dried at 60°C for 8 hours, and crushed in a grinder to obtain C-MMT-4 with an exfoliated structure.

[0051] Example 5

[0052] Take 200g of organic modified MMT with an ion exchange capacity of 80mmol / 100g, add 1800ml of deionized water to form a suspension with a mass fraction of 10%, and stir at 50℃ for 6h;

[0053] Take 0.208 mol (molar amount is 1.3 times the total amount of MMT ion exchange) of melamine phosphate and prepare it into an aqueous solution with a concentration of 0.1 mol / L, slowly add the solution to the sodium-based MMT suspension, heat to 60°C and react for 2 hours, filter, wash and then disperse and repeat 3 times to finally obtain a melamine-montmorillonite (N-MMT) suspension.

[0054] Take 300g of H4[SiW 12 O 40 ], add deionized water to prepare a solution with a concentration of 1 mol / L, and then take An aqueous solution (concentration of 0.5 mol / L, the molar ratio of imidazolium cation to heteropolyacid anion is 2 / 1) is added dropwise to the above suspension, then the temperature is raised to 80°C and the reaction is carried out for 1 hour; filtered and washed with water 3 times, then vacuum dried at 60°C for 8 hours, and crushed in a grinder to obtain C-MMT-5 with an exfoliation structure.

[0055] Example 6

[0056] Take 200g of sodium-based MMT with an ion exchange capacity of 80mmol / 100g, add 1800ml of deionized water to form a suspension with a mass fraction of 10%, and stir at 70℃ for 3h;

[0057] Take 0.24 mol (molar amount is 1.5 times the total amount of MMT ion exchange) of melamine acetate and prepare it into an aqueous solution with a concentration of 0.1 mol / L, slowly add the solution to the sodium-based MMT suspension, keep the temperature at 70°C and react for 2 hours, filter, wash and then disperse and repeat 3 times in sequence to finally obtain a melamine-montmorillonite (N-MMT) suspension.

[0058] Take 220g of H4[SiMo 12 O 40 ] 4 , add deionized water to prepare a solution with a concentration of 1 mol / L, and then take An aqueous solution (concentration of 0.5 mol / L, the molar ratio of imidazolium cation to heteropolyacid anion is 2 / 1) is added dropwise to the above suspension, then the temperature is raised to 50°C and the reaction is carried out for 2 hours; the solution is filtered and washed with water three times, then vacuum dried at 70°C for 7 hours, and crushed in a grinder to obtain C-MMT-6 with an exfoliated structure.

[0059] Example 7

[0060] Take 100g of organic modified MMT with an ion exchange capacity of 70mmol / 100g, add 900ml of deionized water to form a suspension with a mass fraction of 10%, and stir at 80℃ for 2h;

[0061] Take 0.12 mol (molar amount is twice the total amount of MMT ion exchange) of melamine carbonate and prepare it into an aqueous solution with a concentration of 0.1 mol / L, slowly add the solution to the sodium-based MMT suspension, heat to 80°C and react for 3 hours, filter, wash and then disperse and repeat 3 times, finally obtain a melamine-montmorillonite (N-MMT) suspension with a mass fraction of 10%.

[0062] Take 150g of H3[PW 12 O 40 ], add deionized water to prepare a solution with a concentration of 1 mol / L, and then take an equal molar An aqueous solution (concentration of 1 mol / L) was added dropwise to the above suspension, then heated to 80°C and reacted for 2 hours; filtered and washed with water three times, then vacuum dried at 60°C for 8 hours, and crushed in a grinder to obtain C-MMT-7 with an exfoliated structure.

Claims

1. A supramolecular ionic polymer exfoliated nano-montmorillonite, characterized in that: The supramolecular ionic polymer exfoliated nano-montmorillonite contains melamine cations, multifunctional imidazole cations and heteropolyacid anions between its layers, and the three form supramolecular ionic polymer compounds through ionic bonds.

2. The supramolecular ionic polymer exfoliated nano-montmorillonite according to claim 1, characterized in that: The chemical structure of heteropolyacid anion is [PW 12 O 40 ] 3- 、[PMo 12 O 40 ] 3- , [BW 12 O 40 ] 3- 、[BMo 12 O 40 ] 3- 、[SiW 12 O 40 ] 4- 、[SiMo 12 O 40 ] 4- One of them.

3. The supramolecular ionic polymer exfoliated nano-montmorillonite according to claim 1, characterized in that: The chemical structure of the multifunctional imidazolium cation is:

4. The method for preparing supramolecular ionic polymer exfoliated nano-montmorillonite according to claim 1, characterized in that: First, melamine salt is loaded onto the MMT sheet by the aqueous solution ion exchange method, and then heteropolyacid anions and multifunctional imidazole cations with different structures are introduced into the MMT interlayer. The supramolecular ionic polymer ionic compounds are formed between the MMT layers by the in-situ intercalation method, so that the MMT layered structure is expanded to achieve a peeling structure.

5. The method for preparing supramolecular ionic polymer exfoliated nano-montmorillonite according to claim 4, characterized in that The preparation method comprises the following steps: (1) A certain amount of MMT is dissolved in water to form a uniform and stable MMT suspension with a mass fraction of 1% to 10%, and the temperature is gradually raised to 50 to 90°C, stirred for 1 to 6 hours, and set aside; (2) slowly adding a 0.1-1 mol / L melamine phosphate solution to the MMT suspension in step (1) above, and reacting at 60-80° C. for 1.5-3 h; then filtering, washing, and redispersing, and repeating this operation 2-3 times to wash away excess unexchanged melamine phosphate, and finally forming a melamine-montmorillonite suspension with a mass fraction of 1% to 10%; (3) firstly, adding a heteropolyacid containing different anions dropwise into the melamine-montmorillonite suspension of step (2), then adding a polyfunctional imidazole bromide dropwise into the suspension, and then heating to 40-60° C. and reacting for 1-2 hours; (4) The product after the reaction in step (3) is filtered and washed with water for 3 to 5 times, and then vacuum dried at 60 to 80° C. for 6 to 8 hours, and then crushed in a pulverizer.

6. The method for preparing supramolecular ionic polymer exfoliated nano-montmorillonite according to claim 5, characterized in that: In step (1), the MMT is sodium-based MMT or organic-modified MMT, and its cation exchange capacity is 60 to 120 mmol / 100 g.

7. The method for preparing supramolecular ionic polymer exfoliated nano-montmorillonite according to claim 5, characterized in that: In step (2), the molar amount of melamine cations in the melamine phosphate solution is 1.2 to 2 times the total ion exchange amount CEC in the MMT suspension.

8. The method for preparing supramolecular ionic polymer exfoliated nano-montmorillonite according to claim 5, characterized in that: In step (3), the mass of the heteropoly acid is 1.1 to 1.5 times that of montmorillonite, and the concentration is 0.1 to 1 mol / L.

9. The method for preparing supramolecular ionic polymer exfoliated nano-montmorillonite according to claim 5, characterized in that: The anion of the heteropoly acid is [PW 12 O 40 ] 3- or [PMo 12 O 40 ] 3- or [BW 12 O 40 ] 3- or [BMo 12 O 40 ] 3- When the structural formula of the multifunctional imidazole bromide salt is When the molar ratio of the polyfunctional imidazolium cation to the heteropolyacid anion is 1; The structural formula of the multifunctional imidazole bromide is When the molar ratio of the imidazolium cation to the heteropolyacid anion is 1.5 / 1; The anion of the heteropoly acid is [SiW 12 O 40 ] 4- 、[SiMo 12 O 40 ] 4- When the structural formula of the multifunctional imidazole bromide salt is When the molar ratio of the imidazolium cation to the heteropolyacid anion is 4 / 3; The structural formula of the multifunctional imidazole bromide is When the molar ratio of the imidazolium cation to the heteropolyacid anion is 2 / 1.